Molecular diagnosis of Chagas disease in patients with megaesophagus exhibiting negative or inconclusive serological results - Batista, Angelica Martins; Pavan, Tycha Bianca Sabaini; de Almeida, Eros Antonio; de Alcantara, Daniel Maximo Corrêa; Andrade, Paula Durante; Martins, Luiz Cláudio; Wanderley, Jamiro da Silva; Costa, Sandra Cecília Botelho; Marcon, Gláucia Elisete Barbosa (Frontiers in Parasitology, 2025)
Chagasic megaesophagus is a relatively uncommon clinical manifestation in individuals with chronic Chagas disease (CD), and it has not been extensively documented in literature. However, individuals may exhibit negative or inconclusive serology for CD. This study aimed to assess the performance of molecular diagnostics for CD in participants with these conditions. This was a prospective cohort study that included 26 participants with negative or inconclusive conventional CD serology (Group I), 33 participants with positive CD serology and megaesophagus (Group II), and 10 participants with negative serology and no CD epidemiological history (Group III). Blood samples were collected for serological tests (ELISA and IFAT), blood cultures, and molecular tests like nested PCR (nPCR) targeting Sat-DNA and kDNA, as well as quantitative PCR (qPCR) of T. cruzi. Statistical analyses applying the Composite Reference Standard (CRS), showed that diagnosis by Sat-DNA nPCR had a sensitivity of 95% (95% CI: 82%–99%), a specificity of 81% (95% CI: 64%–93%), an accuracy of 88%. When considering a positive result from at least one molecular test, 20 out of 26 participants with megaesophagus and negative or inconclusive conventional serology were identified (76.9%). This study reinforce the greater detection capacity of Sat-DNA nPCR compared to the diagnostic methods tested. This emphasizes the importance of employing molecular diagnosis to clarify the etiology in megaesophagus cases.